2021
DOI: 10.1111/jch.14193
|View full text |Cite
|
Sign up to set email alerts
|

Clinical audit of adherence to hypertension treatment guideline and control rates in hospitals of different sizes in Thailand

Abstract: A clinical audit of hospitals in Thailand was conducted to assess compliance with the national hypertension treatment guidelines and determine hypertension control rates across facilities of different sizes. Stratified random sampling was used to select sixteen hospitals of different sizes from four provinces. These included community (<90 beds), large (90–120 beds), and provincial (>120 beds) hospitals. Among new cases, the audit determined whether (i) the recommended baseline laboratory assessment was comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
4
2
Order By: Relevance
“…Physician preference, especially in tertiary facilities may also influence adherence to generic medication prescribing. Generally, adherence to hypertension treatment guidelines in primary and secondary care has been reported to be suboptimal 55–60 . Several studies have reported lower adherence to hypertension treatment guidelines in primary and secondary care compared to our findings, although two studies reported similar findings 55–60 .…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Physician preference, especially in tertiary facilities may also influence adherence to generic medication prescribing. Generally, adherence to hypertension treatment guidelines in primary and secondary care has been reported to be suboptimal 55–60 . Several studies have reported lower adherence to hypertension treatment guidelines in primary and secondary care compared to our findings, although two studies reported similar findings 55–60 .…”
Section: Discussioncontrasting
confidence: 76%
“… 55 , 56 , 57 , 58 , 59 , 60 A study in Thailand reported drug treatment guideline adherence of 9%–59.7% in small community and medium sized nonreferral hospitals. 55 In primary healthcare settings, a study in South Africa found treatment guideline adherence of 56.6%. 56 These findings were corroborated by findings in district health clinics in a district in Malaysia.…”
Section: Discussionmentioning
confidence: 99%
“…4 5 The factors associated with uncontrolled BP reported in the literature are described as patient related, medication related and healthcare system related. [6][7][8][9] The patient oriented factors include sociodemographic and clinical characteristics as well as patient's knowledge about HT. It is frequently reported that patients with HT are least knowledgeable on normal BP values and lifestyle changes during the treatment process.…”
Section: Open Accessmentioning
confidence: 99%
“…The factors associated with uncontrolled BP reported in the literature are described as patient related, medication related and healthcare system related 6–9. The patient oriented factors include sociodemographic and clinical characteristics as well as patient’s knowledge about HT.…”
Section: Introductionmentioning
confidence: 99%
“…Thai Hypertension Society guidelines on the treatment of hypertension also suggest using single-pill combination drugs for treating hypertension in the Thai population [ 39 ]. However, the prescription of single-pill combination drugs is extremely low in governmental hospitals of different sizes in Thailand [ 57 ]. Therefore, using single-pill combination drugs is also encouraged to improve medication adherence.…”
Section: Introductionmentioning
confidence: 99%